KONSUMSI PANGAN DAN GIZI SERTA SKOR POLA PANGAN HARAPAN PADA DEWASA USIA 19—49 TAHUN DI INDONESIA - Anwar, Khoirul; Hardinsyah, Hardinsyah (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to assess food consumption, nutritional dietary quality (NDQ), Desirable Dietary Pattern (DDP) scores, and the correlation between DDP and NDQ of adults aged 19—49 years. This study used data of Basic Health Research (Riskesdas) 2010 in the form of consumption data taken with the 24-hour recall method. The survey showed that the grains consumed by the most of subjects (99.4%), while the oily seeds are consumed by the smallest number (2.0%). The mean of DDP Score was 53.1±9.3 (54.6±9.5 for men and 51.7±9.1 for women). The mean of the 4 nutrients NDQ was 62.8±20.6 and for 10 nutrients NDQ was 51.1±15, while the 14 nutrients NDQ was 54.1±16.1. The correlation between DDP score and NDQ’s was 0.65 to 0.72, so the DDP assessment could be used to evaluate dietary diversity and nutritional quality for adult diet.